Medicinal and aromatic plants keep us healthy and wealthy - Kumar, T Vasantha (Indian Horticulture, 2019)
There are a number of medicinal and aromatic plants grown in our country. They are serving humans being since time imemorial. Their portential need to be tapped at urgent basis. Good R&D efforts have been made. Therefore, they need to be popularized at mass scale. It is high time to bring the glory back of this valued green economy in our country.